Association of Presence and Severity of Thrombocytopenia with Types and Severity of Malaria - Imran , Muhammad; Badshah , Aliena; Naeem, Hammad; Ahmad , Zeeshan; Ahmed, Khaqan; Shah, Syed Junaid (Indus Journal of Bioscience Research, 2025)
Malaria is a significant community health problem in affected areas such as Pakistan, the most prevalent causing parasitic species being Plasmodium vivax and Plasmodium falciparum. Very common hematological symptoms include thrombocytopenia, which is often seen in the two species. This cross-sectional research paper set out to establish the prevalence and degree of thrombocytopenia in malaria sufferers as well as evaluating the relationship with Plasmodium species. The study was completed in six months at Khyber Teaching Hospital, Peshawar and involved 85 microscopical-confirmed malaria cases. Platelet count (per microliter) was recorded and subdivided according to mild (50,001-150,000/ uL, moderate (20,000- 50,000/ uL) and severe (